Coordination Compounds of 9, 10‐Dihydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐Oxide (DOPO) Ligands: Extremely High Thermostability and Ligand Oxidation in the Solid State. Issue 25 (23rd June 2020) - Goedderz, Daniela; Schäfer, Timmy; Klitsch, Johannes; Weber, Lais; Weber, Bettina; Fuhr, Olaf; Buntkowsky, Gerd; Schönberger, Frank; Döring, Manfred
Abstract : Different metal phosphinates and phosphonates were obtained containing zinc, calcium and magnesium as cations by means of a salt metathesis reaction with sodium salts of DOPO and DOPO‐OH. The synthesized complexes [Zn(DOPO)2 ] n, [Zn(DOPO‐OH)2 ] n and [Ca(DOPO)2 (H2 O)] n are featured a polymeric structure. The open‐ring metal phosphinate coordination compound [Zn(DOPO)2 ] n is able to undergo a non‐reversible thermally induced oxidative cyclisation to the corresponding metal phosphonate [Zn(DOPO‐OH)2 ] n . The magnesium and calcium phosphinates cannot be oxidized to their corresponding metal phosphonate complexes. All organophosphorus compounds were analyzed by means of X‐ray crystallography, NMR, TGA and TDMS. The oxidative cyclisation reaction of [Zn(DOPO)2 ] n was investigated by DSC. Additionally, the coordination polymer [Zn(DOPO)2 ] n can be transformed into a molecular complex by adding nitrogen ligands such as N ‐methylimidazole, whereby the phosphonate ligand changes from a bridging to a monodentate ligand. The synthesized coordination compounds exhibit very high thermostabilities of up to 520 °C. Abstract : Front view of the crystal structure of [Zn(DOPO‐OH)2 ] n (H atoms omitted for clarity). The synthesized coordination compounds have specific characteristics like outstanding thermostabilities up to 520 °C or polymeric structures. [Zn(DOPO‐OH)2 ] n can be synthesized by salt metathesis or by an oxidative click mechanism starting from [Zn(DOPO)2 ] n . The thermal behavior of the compounds was investigated in detail by TDMS, 31 P CP MAS, and 13 C CP MAS.